Partisipasi Perempuan Dalam Pengembangan Desa Wisata Kembangarum, Sleman, Yogyakarta - Ramadita Adinda Fitri; Royanow Achlan Fahlevi; Rahayu Mia; Yudha Sakti Pratama (Journal of Tourism Destination and Attraction, 2022)
This research is motivated by the presence of women who as an actors in the development of tourist villages. This study aims to increase the level of women's participation in developing the tourism village of Kembangarum. This study used a qualitative method aimed at determining the level of women's participation in the development of a tourism village in the Tourism Village of Kembangarum with a total of 12 participants consisting of 10 women, 1 manager and 1 as a headman. The results of the study found that women's participation in tourism activities was still not optimal as seen from the participation process consisting of decision making, activity implementation, evaluation and utilization of the results which were not comprehensive. Even though, the activities held in the Kembangarum Tourism Village can improve the quality of life of the women who live around the Kembangarum Tourism Village, especially in economic and social aspects. This research was conducted to develop women's participation in order to optimize women's involvement in village development through activities organized by managers in Kembangarum Tourism Village